The effect of a switch in housing systems on the welfare of gilts: does experience matter? - Smid, Anne-Marieke (SLU/Dept. of Animal Environment and Health (until 231231), 2014)
In general, three approaches towards animal welfare exist: animal bodies, natures and minds. These concepts respectively emphasise physical health, natural behaviour and mental health. Each approach has its own corresponding welfare indicators. Knowledge in the area of especially the more persistent emotional states (mental health) of animals is lagging behind. This has to be improved, since the assessment of the emotional states of animals is a crucial step in improving their welfare.